2008
DOI: 10.1063/1.2883950
|View full text |Cite
|
Sign up to set email alerts
|

Linewidth enhancement factor of terahertz quantum cascade lasers

Abstract: The linewidth enhancement factor (LEF) of terahertz quantum cascade lasers is measured using an optical feedback self-mixing technique. As expected, a much lower LEF is found than is common for interband lasers, but instead of the predicted value of zero, the LEF depends on the laser conditions and can be as high as 0.5. The measured value tends to increase with increasing current. Cross absorption within the laser active region is suggested as a possible cause for the nonzero LEF observed. (C) 2008 American I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
45
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 95 publications
(52 citation statements)
references
References 9 publications
7
45
0
Order By: Relevance
“…It has been demonstrated that thermal photons contribute significantly to linewidth broadening at elevated temperatures. For the investigated structure of 3 THz QCL, a linewidth enhancement factor of a % 0.5 is found, which is in excellent agreement with experimental results (Green et al 2008). Mátyás et al (2011) performed calculations of photon-induced transport in mid-infrared QCL structures (Bai et al 2010).…”
Section: Optical Gainsupporting
confidence: 63%
“…It has been demonstrated that thermal photons contribute significantly to linewidth broadening at elevated temperatures. For the investigated structure of 3 THz QCL, a linewidth enhancement factor of a % 0.5 is found, which is in excellent agreement with experimental results (Green et al 2008). Mátyás et al (2011) performed calculations of photon-induced transport in mid-infrared QCL structures (Bai et al 2010).…”
Section: Optical Gainsupporting
confidence: 63%
“…For example, variation of L ext (t) with time may represent a moving target or changes in surface relief during a raster scan over the object surface [16]; time variation of ε(t) or R(t) may represent an optical chopper in the collimated beam path; and the target reflectivity R may be a complex number for the purpose of a refractive index measurement [18]. The linewidth enhancement factor of THz QCLs, α in (2), is low and known to vary slightly with drive current and optical feedback [56]. In this work we use the value α = −0.1 [9].…”
Section: Incorporating Optical Feedbackmentioning
confidence: 99%
“…Consequently, QC lasers should display a symmetric differential gain and a zero α [16]. However, experiments determined nonzero values going from α = 0 to α = 2 [17]- [20].…”
Section: Formulationmentioning
confidence: 99%
“…It is also worthwhile to stress that Eqs. (18)- (20) are not the equations for a Class A injected laser. For a Class A laser (such as He-Ne and Ar + lasers), the carrier Z is adiabatically eliminated and α = 0 [1].…”
Section: Fast Escape Of Carriers At the Lower Levelmentioning
confidence: 99%